Enhancing Line Efficiency Performance at Assembly Line Using Ecrs-Based Line Balancing Concept - Amalia Syaharani Ibnu; Annisa Uswatun Khasanah (Teknoin, 2023)
Recently Indonesian textile and garment manufacturer has experienced a problem with shop floor production. The complexities in the manufacturing process led to many problems such as the inefficiency, and thus prevented the company from achieving its target. In fact, even though the company has established the efficiency target of 80%, the production floor cannot realize it. Thus, this research aims to increase the line efficiency to reach the company’s target. At the beginning of the analysis, the efficiency of assembly line was only 51,68%. Since, this value did not meet the company’s target and was not satisfying; the concept of ECRS was applied. The purpose of this research is to simplify the method to provide better effect and process flow. Before applying the method, the fishbone diagrams were used. The factors of man, method, machine and measurement were used to describe the root cause of the losses. Thus, after applying the concept of ECRS, the efficiency level increased to 81,54%, which had met the company’s target. The assembly line will run better and smoother with the smaller possibility of bottleneck if all of the workstations have a relatively balanced workload.